Trichoderma citrinoviride: Anti-Fungal Biosurfactants Production Characteristics - Piegza, Michał; Szura, Kamil; Łaba, Wojciech (Frontiers in Bioengineering and Biotechnology, 2021)
The mechanism of direct impact of Trichoderma fungi on other organisms is a multilayer process. The level of limiting the growth of other microorganisms is determined by the strain and often by the environment. Confirmation of the presence of extracellular biosurfactants in certain strains of Trichoderma considered as biocontrol agents was regarded as a crucial topic complementing the characterization of their interactive mechanisms. Selected strains of T. citrinoviride were cultured in media stimulating biosurfactant biosynthesis, optionally supplemented with lytic enzyme inducers. Results confirmed the anti-fungal properties of surface-active compounds in the tested culture fluids. Preparations that displayed high fungal growth inhibition presented marginal enzymatic activities of both chitinases and laminarinases, implying the inhibitory role of biosurfactants. Fractions from the foam of the culture fluid of the C1 strain, cultured on Saunders medium, and HL strain on MGP medium, without an additional carbon source, exhibited the most prominent ability to inhibit the growth of phytopathogens. Filamentous fungi capable of producing fungicidal compounds, including surfactants, may find applications in protecting the plants against agri-food pathogenic molds.